Efforts to Improve Dribbling Skills Through Agility Training in Futsal Games SMA Negeri 2 Wonogiri - Rizky Giri Prayoga; Gatot Jariono; Pungki Indarto (Journal Physical Education, Health and Recreation, 2025)
The purpose of this study is to determine the effect of agility training on dribbling skills in the futsal extracurricular of SMA Negeri 2 Wonogiri. The research design used was an experiment and the instrument in this study used a dribbling test, with a research sample of 20 extracurricular futsal children of SMA Negeri 2 Wonogiri. From the results of the research that has been carried out, the results of data analysis and data processing, it was found that there is an effect of agility training on dribbling skills in futsal games carried out by SMA Negeri 2 Wonogiri students, especially male students. This can be seen from the results of the average score obtained when conducting the initial test as many as 65% of students have not met the criteria for passing the agility test. And after giving Treatment There is a significant increase in results that can be seen from the results Post-Tests The results obtained were that 95% of the children met the time criteria specified when conducting the agility test. So it can be concluded that there is a significant influence of agility training on dribbling skills in the futsal extracurricular of SMA Negeri 2 Wonogiri.